2016
DOI: 10.3791/53431
|View full text |Cite
|
Sign up to set email alerts
|

Hollow Fiber Bioreactors for <em>In Vivo</em>-like Mammalian Tissue Culture

Abstract: Tissue culture has been used for over 100 years to study cells and responses ex vivo. The convention of this technique is the growth of anchorage dependent cells on the 2-dimensional surface of tissue culture plastic. More recently, there is a growing body of data demonstrating more in vivo-like behaviors of cells grown in 3-dimensional culture systems. This manuscript describes in detail the set-up and operation of a hollow fiber bioreactor system for the in vivo-like culture of mammalian cells. The hollow fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…At first, the design, construction and verification of the overexpressing lentivirus would incur some costs, but the subsequent plasmid amplification and lentivirus packaging would be relatively inexpensive. In the future, with the help of new technology, including hollow fiber bioreactors [], which have the potential to greatly enhance the harvest rate of exosomes, the consumption of exosomes would be less and less. Therefore, exosome‐based therapy could become a promising mainstream future therapy strategy.…”
Section: Discussionmentioning
confidence: 99%
“…At first, the design, construction and verification of the overexpressing lentivirus would incur some costs, but the subsequent plasmid amplification and lentivirus packaging would be relatively inexpensive. In the future, with the help of new technology, including hollow fiber bioreactors [], which have the potential to greatly enhance the harvest rate of exosomes, the consumption of exosomes would be less and less. Therefore, exosome‐based therapy could become a promising mainstream future therapy strategy.…”
Section: Discussionmentioning
confidence: 99%
“…In further support that differentiated SH-SY5Y cells have many of the characteristics of neurons, removal of BDNF results in cellular apoptosis. This suggests that survival of differentiated SH-SY5Y cells is dependent on trophic factors, similar to mature neurons [ 41 ]. Alox15 mRNA expression was significantly increased after treatment with general HDAC inhibitors TSA and sodium butyrate and the Class I HDAC inhibitors MS-275 and depsipeptide, in undifferentiated SH-SY5Y cells.…”
Section: Discussionmentioning
confidence: 99%
“…Overall it was shown that PX membranes supported B13 attachment, viability and function at levels equivalent or greater than glass and TCPS controls, suggesting that these materials are ideally suited for use in cell culture applications – specifically for the generation of bioartificial liver devices based on membrane bioreactors. Indeed, PX40 hollow fibres have already been applied in such a system [1] . The fibres could be of interest for incorporation into commercial HF systems such as FiberCell, Terumo or Cellab, and in theory, any HF application where cells are currently cultured on standard tissue culture polystyrene.…”
Section: Discussionmentioning
confidence: 99%
“…The use of membranes as cell scaffolds is of key interest in the development of in vitro drug screening assays. Cells cultured in membrane bioreactors experience a more in vivo- like environment than those in traditional two-dimensional cell culture [1] . Culturing cells under physiologically relevant conditions can create more realistic and accurate metabolic responses to drug testing [2] , [3] .…”
Section: Introductionmentioning
confidence: 99%